Insights Into Mucosal Innate Immune Responses in House Dust Mite-Mediated Allergic Asthma - Abu Khweek, Arwa; Kim, Eunsoo; Joldrichsen, Marisa R.; Amer, Amal O.; Boyaka, Prosper N. (Frontiers in Immunology, 2020)
The prevalence of asthma has been rising steadily for several decades, and continues to be a major public health and global economic burden due to both direct and indirect costs. Asthma is defined as chronic heterogeneous inflammatory diseases characterized by airway obstruction, mucus production and bronchospasm. Different endotypes of asthma are being recognized based on the distinct pathophysiology, genetic predisposition, age, prognosis and response to remedies. Mucosal innate response to environmental triggers such as pollen, cigarette smoke, fragrances, viral infection and house dust mites (HDMs) are now recognized to play an important role in allergic asthma. HDMs are the most pervasive allergens that co-habitat with us, as they are ubiquitous inhouse dusts, mattress and bedsheets, and feed on a diet of exfoliated human skin flakes. Dermatophagoides pteronyssinus, is one among several HDMs identified up to date. During the last decade, extensive studies have been fundamental in elucidating the interactions between HDM allergens, the host immune systems and airways. Moreover, the paradigm in the field of HDM-mediated allergy has been shifted away from being solely a Th2 geared to an orchestrated response that is dictated via extensive crosstalk between the epithelium, professional antigen presenting cells (APCs) and components of the adaptive immunity. In fact, HDMs have several lessons to teach us about their allergenicity, the complex interactions that stimulate innate immunity in initiating and perpetuating the lung inflammation. Herein, we review main allergens of Dermatophagoides pteronyssinus and their interactions with immunological sentinels that promote allergic sensitization and activation of innate immunity, which is critical for the development of the Th2 biased adaptive immunity to HDM allergens and development of allergic asthma.